Ap4b1-knockout mouse model of hereditary spastic paraplegia type 47 displays motor dysfunction, aberrant brain morphology and ATG9A mislocalization. Issue 1 (6th January 2023) - Scarrott, Joseph M; Alves-Cruzeiro, João; Marchi, Paolo M; Webster, Christopher P; Yang, Zih-Liang; Karyka, Evangelia; Marroccella, Raffaele; Coldicott, Ian; Thomas, Hannah; Azzouz, Mimoun
Abstract: Mutations in any one of the four subunits (ɛ4, β4, μ4 and σ4) comprising the adaptor protein Complex 4 results in a complex form of hereditary spastic paraplegia, often termed adaptor protein Complex 4 deficiency syndrome. Deficits in adaptor protein Complex 4 complex function have been shown to disrupt intracellular trafficking, resulting in a broad phenotypic spectrum encompassing severe intellectual disability and progressive spastic paraplegia of the lower limbs in patients. Here we report the presence of neuropathological hallmarks of adaptor protein Complex 4 deficiency syndrome in a clustered regularly interspaced short palindromic repeats-mediated Ap4b1 -knockout mouse model. Mice lacking the β4 subunit, and therefore lacking functional adaptor protein Complex 4, have a thin corpus callosum, enlarged lateral ventricles, motor co-ordination deficits, hyperactivity, a hindlimb clasping phenotype associated with neurodegeneration, and an abnormal gait. Analysis of autophagy-related protein 9A (a known cargo of the adaptor protein Complex 4 in these mice shows both upregulation of autophagy-related protein 9A protein levels across multiple tissues, as well as a striking mislocalization of autophagy-related protein 9A from a generalized cytoplasmic distribution to a marked accumulation in the trans -Golgi network within cells. This mislocalization is present in mature animals but is also in E15.5 embryonic cortical neurons. Histological examination of brain regions also shows an accumulation of calbindin-positive spheroid aggregates in the deep cerebellar nuclei of adaptor protein Complex 4-deficient mice, at the site of Purkinje cell axonal projections. Taken together, these findings show a definitive link between loss-of-function mutations in murine Ap4b1 and the development of symptoms consistent with adaptor protein Complex 4 deficiency disease in humans. Furthermore, this study provides strong evidence for the use of this model for further research into the aetiology of adaptor protein Complex 4 deficiency in humans, as well as its use for the development and testing of new therapeutic modalities. Abstract : Scarrott et al . report a recently generated clustered regularly interspaced short palindromic repeat-mediated mouse model of hereditary spastic paraplegia 47 displays neuroanatomical and behavioural deficits consistent with those observed in human patients and concordant with previous studies in other mouse models of adaptor protein Complex 4 deficiency. Graphical Abstract: Graphical abstract